Adenovirus-mediated downregulation of the ubiquitin ligase RNF8 sensitizes bladder cancer to radiotherapy - Zhao, Mei-Jun (Oncotarget, 2016)
The ubiquitin ligase RNF8 promotes the DNA damage response (DDR). We observed that the expression of RNF8 was increased in bladder cancer cells and that this change in RNF8 expression could be reversed by adenovirus-mediated shRNA treatment. Moreover, we found that RNF8 knockdown sensitized bladder cancer cells to radiotherapy, as demonstrated by reduced cell survival. Additionally, the absence of RNF8 induced a high rate of apoptosis and impaired double-strand break repair signaling after radiotherapy. Furthermore, experiments on nude mice showed that combining shRNF8 treatment with radiotherapy suppressed implanted bladder tumor growth and enhanced apoptotic cell death in vivo. Altogether, our results indicated that RNF8 might be a novel target for bladder cancer treatment.